FEATURES OF THE DEVELOPMENT OF URBAN PLANNING: DIGITALIZATION AND TRANSFORMATIONAL CHANGES - Крисоватий, Ігор А. (Journal of Strategic Economic Research, 2024)
The development of urbanism in the modern world is significantly influenced by digitization and transformational changes. The main components of modern urban planning are: the development of smart technologies to optimize the management of urban resources, such as energy, water, transport and others; implementation of digital monitoring systems to ensure the efficient operation of city infrastructure and improve the quality of services; application of sensors and IoT to collect and process data from the urban environment; development of "smart" systems, such as smart houses, smart parking, smart transport and others. Thus, the purpose of the presented work is to determine the features of the development of urbanism under the influence of transformational changes and digitalization. The main methods of the presented research are: the method of comparison to determine the modern trends of urbanism, the methods of induction and deduction to establish the main components of urbanism that were formed under the influence of digitalization and transformational changes, the methods of analysis and synthesis to establish the sequence of implementation of complex actions to ensure the development of urbanism, the graphic method for a visual representation of individual research results. Thus, urbanism is important for creating urban environments that are efficient, sustainable, livable and responsive to the needs of different social groups. Modern challenges such as urban intensification, climate change and digital transformation make urbanism an even more relevant and complex field. The main characteristic features of urbanism are: the use of large volumes of data for forecasting and optimization of various aspects of urban life; data analysis for decision-making in the fields of transport, energy, social services and others; involving the public through digital means for decision-making and city development planning; using online platforms to discuss ideas, collect feedback and interact between residents and authorities; development of mobile applications to facilitate urban life, including mobile public transport, navigation, mobile health services and others; providing access to information and services through modern mobile technologies; introduction of electronic services for interaction between residents and the authorities; digital solutions to optimize management processes and ensure transparency of power structures; the use of digital technologies for production and construction, such as 3D printing of buildings, virtual reality (VR) and others; creation of energy-efficient and sustainable buildings using modern technologies; ensuring cyber security in the conditions of the growing number of digital services and devices connected to the network; development of strategies and technologies to protect city systems from cyber threats. Digitization and transformational changes in urban planning help to create more efficient, convenient and sustainable urban environments, contributing to the improvement of the quality of life of residents and optimization of city management.